Analisis Sektor Unggulan Perekonomian Daerah (Studi pada Komoditi Unggulan di Kecamatan Bumiaji Kotamadya Batu) - Sugeng Hadi Utomo (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
This research aims to determine the economic profile of district Bumiaji. Municipal Batu and what commodities are the main of the district Bumiaji, Municipal of Batu. This research is an explorative research that is exploring the economic potential existing in the area for quantitative descriptive analysis. Type of this research is suitable for problem that has not been much attention in the discussion. The object of this research is the regional economic from district of Bumiaji, municipal of Batu, East Java. The results showed the economic profile of district Bumiaji, municipal Batu characterized by agricultural sector. Leading commodities are apples, vegetables and flower plants. Various plants are scattered in various take Sumberejo, Gunungsari and Punten villages. The development potential of the region should pay attention to aspect of sustainability and competitive ness of market. The dynamics of regional economic development oriented to product competitive advantage.Keywords: The regional economic, commodities